Biochemical Characterization of β‐Amino Acid Incorporation in Fluvirucin B2 Biosynthesis. (14th May 2018) - Barajas, Jesus F.; Zargar, Amin; Pang, Bo; Benites, Veronica T.; Gin, Jennifer; Baidoo, Edward E. K.; Petzold, Christopher J.; Hillson, Nathan J.; Keasling, Jay D.
Abstract: Naturally occurring lactams, such as the polyketide‐derived macrolactams, provide a diverse class of natural products that could enhance existing chemically produced lactams. Although β‐amino acid loading in the fluvirucin B2 polyketide pathway was proposed by a previously identified putative biosynthetic gene cluster, biochemical characterization of the complete loading enzymes has not been described. Here we elucidate the complete biosynthetic pathway of the β‐amino acid loading pathway in fluvirucin B2 biosynthesis. We demonstrate the promiscuity of the loading pathway to utilize a range of amino acids and further illustrate the ability to introduce non‐native acyl transferases to selectively transfer β‐amino acids onto a polyketide synthase (PKS) loading platform. The results presented here provide a detailed biochemical description of β‐amino acid selection and will further aid in future efforts to develop engineered lactam‐producing PKS platforms. Abstract : Beta‐(amino acid) testing : We provide a detailed biochemical description of β‐amino acid selection, incorporation, and promiscuity in the fluvirucin B2 loading pathway, such as the pathway′s ability to use various amino acids as starter units and aminoacylating groups. We provide new insights into the flexibility of β‐amino acid selection in polyketide biosynthesis by introducing non‐native acyltransferases.